Pripovedne strategije v reprezentacijah nasilja - Matajc, Vanesa (Primerjalna književnost, 2016)
The article looks at the narration of ethnocide through a comparative reading of two contemporary Bosnian novels (Ključanin's Pričevalec and Karahasan's Nočni shod) about the Bosnian War (1992-1995) against the historical and literary backdrop of other selected novels that thematize nationalisms in the Yugoslav Wars and their effects. The comparison reveals recourse to testimonial discourse and the attendant use of "non-mimetic" narrative strategies of temporality ("circular," "melded") as a common narrative strategy. These are attended, moreover, by the specific treatment of the motif and theme of "the spectre," which evokes the Islamic religious context and the cultural-historical embeddedness of the narrative and which at the same time facilitates the intrusion of the fantastic or even a reading in the magical realist code.
Keywords: Ključanin, Zilhad: Pričevalec; Karahasan, Dževad: Nočni shod; bosanska književnost; bošnjaška književnost; sodobni bosanski romani; vojne; Bosna in Hercegovina; Bosnia and Herzegovina; etnično nasilje; narativne strategije časovnosti; fantastika